THE NOTION OF PRUDENCE IN ARISTOTLE AND THE CRISIS OF LEADERSHIP IN NIGERIA (2012)
Two schools of thought, the Moralist School and the Realist School, have discussed the problem of leadership. Moralists have called for an explicit recognition of the moral nature of leadership but failed to provide leaders with a consistent direction of what ethical leadership should be. Realists argue for a total autonomy of the political sphere. They fail to recognize the existence and relevance of any moral consideration in the political arena; consequently, they subordinate moral standards to those of politics. The ideological confusion arising between both schools of thought is responsible for the absence of an adequate and consistent theory of political leadership. This study, therefore, seeks to provide a theory of political leadership that will constitute a viable framework for good leadership in Nigeria. Aristotle’s notion of prudence which states that prudent judgment is a central moral resource for political leaders was adopted for this research. The study employed the method of conceptual analysis to clarify the concepts of virtue, prudence and leadership. The reconstructive method was also used to synthesize basic elements of the moralist and the realist schools of thought with Aristotle’s notion of prudence. Aristotle’s Nicomachean Ethics, David Notions’ Democracy and Moral Development and A Politics of Virtue and Otto Gierke’s Natural Law and the Theory of Society, constitute some of the primary texts for this study. Texts and other library and archival materials used were subjected to content analysis. Bad political leadership in Nigeria has continued to be one of the root causes of crisis in the nation. This problem is generated by the lack of an acceptable and consistent theory of leadership. There is also the absence of a standard guideline and framework to guide leaders in their daily decision making processes. Moralist insists that an explicit recognition of the moral nature of leadership must be given due priority. However, this opinion failed to provide leaders with a consistent guideline of what the essence of ideal leadership should be. Realists maintain that universal moral principles cannot be applied to the actions of political leaders in their abstract universal formulation, but that they must be filtered through the concrete circumstances of time and place. This realist position creates detached and selfless leaders who allow nothing get in their way of achieving successful political actions. Leadership crisis in Nigeria arises as a result of the absence of practical prudence, which is a core virtue in Aristotle’s ethics. Prudent judgment is required to identify the salient aspects of political situations which leaders have obligations to consider before making political decisions. The guidelines prescribed by Aristotle in making prudent judgment include: Disciplined reason and openness to experience; Foresight, Deploying power; Timing and momentum; Proper relation of means and ends; Durability and legitimacy of outcomes; and Consequences for community. Aristotle’s notion of prudence, therefore, provides a consistent guideline for drastically reducing the scourge of bad leadership in Nigeria. Its practical adoption would enhance the quality of political leadership in Nigeria.